Strengthening Teacher Capacity in the use of Interactive Learning Media (Neolectura, 2023)
This research focuses on strengthening teacher capacity through the use of interactive learning media in an effort to increase student participation in the learning process. The use of interactive learning media is considered important to create a more enjoyable and effective learning experience for students as well as improve the overall quality of learning. This study aims to provide understanding and training to teachers about the capabilities and potential of interactive learning media in facilitating a more interactive and interesting learning process. The method used in this study is a workshop where teachers are given an understanding of the concept of interactive learning media and its use in the learning process. The workshop results showed that most of the teachers (70%) showed an interest in continuing to develop the use of the Nearpod application as a learning medium because they realized the importance of this application in increasing students' creativity. However, some other teachers (30%) still feel the need for further intervention to be more proficient in utilizing this learning medium optimally. In conclusion, interactive learning media is an important part of the learning process for teachers because it can increase student engagement and motivation. Increasing teacher capacity to utilize interactive learning media is considered an important step to achieving optimal learning outcomes. It is hoped that the results of this research can contribute to developing more effective and innovative learning strategies in the world of education.